Scapegoats and transparency in organizations - Björn Segendorff (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
A separating equilibrium in which competent (incompetent) leaders choose competent (incompetent) co-workers is investigated. An outside observer rewards the leader at good policy outcomes. The incompetent co-worker can, at bad outcomes, be used as scapegoat. By assumption, the leader may fail in blaming the scapegoat. Two different assumptions on the outside observer's information set are compared. If she cannot observe a failed attempt, the separating equilibrium exists only if two non-mimicking constraints are met. If she can observe a failed attempt, an additional constraint is added due to the possibility of partial mimicking.
Keywords: C72; D72; D82; J33; 330; Separating equilibrium; competence; transparency; co-worker; blame